The MISDIRECTION OF REPUBLICAN BRAZIL OF ANTONIO CALLADO: A READING OF REFLEXOS DO BAILE. (TEL Tempo, Espaço e Linguagem, 2022)
Published in 1976, Reflexos do Baile by Antonio Callado is a kaleidoscopic novel. In this research, we will analyze the allegorical interaction identified in that fiction among the early years after the proclamation of the Brazilian Republic and the historical time of the Costa e Silva and Médici dictatorships. For that, we will explore between the subtext of this literary text certain historical indications and, in the sequence, unfold them analytically. We are interested in phenomena that are catalysts of approximation between the two historical times mentioned above, namely, state violence and the manipulation of history. The conclusion is that in Reflexos Callado records the resistance of the losers and positions itself against the manipulation of the history of Brazil.